A Beurling-Helson type theorem for modulation spaces. Issue 1 (2009) - Okoudjou Okoudjou, Kasso A. Kasso A.
Abstract : We prove a Beurling-Helson type theorem on modulation spaces. More precisely, we show that the only 𝒞 1 changes of variables that leave invariant the modulation spaces ℳ p, q (ℝ d ) are affine functions on ℝ d . A special case of our result involving the Sjöstrand algebra was considered earlier by A. Boulkhemair.